The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.22610/jebs.v11i2(j).2819
|View full text |Cite
|
Sign up to set email alerts
|

Trade in Services-Economic Growth Nexus: An Analysis of the Growth Impact of Trade in Services in SADC Countries

Abstract: The article analysed the trade in services led growth in ten selected countries in the Southern African Development Community region using econometric regression models. Panel data obtained from the World Bank and United Nations Conference on Trade and Development databases for the period 1992 to 2015 was analysed. Five variables were used in the econometric analysis. The marginal effects of service and goods exports were positive while those of goods and service imports were negative and highly significant as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…In other words, TO shows a significant effect on economic development, endorsing the tradeinduced growth hypothesis. Our findings support the prevailing literature and empirical confirmation presented by a case study of SADC nations by Maune (2019), a study related to Turkey by (Alsamara, Mrabet et al 2019), and a study of BRICS economies by Rani and Kumar (2019). Likewise, some studies contrasted with our findings, such as Olaifa et al (2013) and .…”
Section: The Long-run Impact Of Selected Macroeconomic Variables On Economic Developmentsupporting
confidence: 92%
“…In other words, TO shows a significant effect on economic development, endorsing the tradeinduced growth hypothesis. Our findings support the prevailing literature and empirical confirmation presented by a case study of SADC nations by Maune (2019), a study related to Turkey by (Alsamara, Mrabet et al 2019), and a study of BRICS economies by Rani and Kumar (2019). Likewise, some studies contrasted with our findings, such as Olaifa et al (2013) and .…”
Section: The Long-run Impact Of Selected Macroeconomic Variables On Economic Developmentsupporting
confidence: 92%
“…Also, Tang et al, (2019) investigate economic expansion as a product of openness for the Mauritius economy. The result revealed a positive but weak contribution of openness to economic expansion and is similar to the study of Maune (2019).In a related study, Alsamara (2019) revealed that trade openness and financial development contributes positively to the economic advancement in Turkey. This evidence is consistent with a handful of previous studies (see Gungor et al, 2014;Gungor & Katircioglu 2010).…”
supporting
confidence: 74%
“…Policy makers for example argued that trade globalization is good for the country as there are development opportunities that accompany free trade, such as transfer of technology which improves productivity and hence results in economic growth (see Cloutier et al 2008). On the contrary, Maune (2019) found that the relationship between goods and service imports and economic expansion was negative and significantly concretized. In some related studies, the civil society holds the position that trade globalization does not result in much gains for segments of the population such as farmers, who tend to be the greatest causalities of globalization (Morrissey and Mold 2006;Utkulu et al 2004;Moon 1997;Greenaway and Sapsford 1994;Shafaedin 1994;Agosin 1991).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…It argues that globalization is an economic detriment to the developing world. Modern researchers such as Morrissey and Mold ( 2006 ), Ogujiuba and Omoju ( 2013 ), and Maune ( 2019 ) have in a way or the other concur with this theory. However, modern blueprint of internationalization and globalization through FDI is evident in transferring technology and human capital to accompany or support the local firms to produce the intended economic development (see Rahman & Mamun, 2016 ; Rani & Kumar, 2019 ).…”
Section: Introductionmentioning
confidence: 93%